OPTIMIZATION OF THE LIBRARY FOR SCHOOL LITERACY MOVEMENT - Dwi Purwanti (Universitas Sebelas Maret, 2018)
The library in a school can be said to be the heart because it is a source of information for teachers and students.The library provides opportunities for students to expand and deepen their knowledge by reading various books.Thus, the library facilitates school residents to find information and knowledge needs and skills needed such as today, including literacy skills.The fact that exists today is that the use of libraries is less organized, the arrangement of books is less neat, and the number of inadequate books is an obstacle in increasing students' interest in reading activities.This study focused on: (1) what is the school literacy movement ?; (2) how to optimize the library for school literacy movements? The results of this study include: (1) school literacy movement is an effort or participatory activity involving all school residents to increase students' interest in reading;(2) optimization of the library carried out by making library activity programs, implementing library programs, and giving rewards related to library programs.